Harmonious Husband and Wife Relationship: : Recognise Dyadic Coping Skills and Spousal Relationship Satisfaction - Rita Markus Idulfilastri; Mandy Ramadhanty Khaerunissa; Siti Marziah Zakaria (PT Publikasiku Academic Solution, 2024)
A harmonious marriage is associated with spousal satisfaction. However, in Indonesia, the divorce rate increases every year. Maintaining a harmonious family takes effort from the spouses and is discussed using stimulus, value and role theories, as internal factors. The external factor is dyadic coping, which is the ability of couples to cope with pressure together and is discussed using the systematic transactional model-STM. The purpose of the study was to determine the effect of dyadic coping on the achievement of harmonious relationships in husbands and wives. Method: non-experimental quantitative with cross sectional technique. Sample characteristics are heterosexual couples who have been married for at least 1 year, aged over 20 years, as many as 150 couples or 300 participants. Relationship satisfaction measurement tool, The Perceived Relationship Quality Components Inventory (PRQC), Cronbach Alpha reliability coefficient = 0.978, while Dyadic Coping is measured by Dyadic Coping Inventory (DCI), Cronbach Alpha reliability coefficient = 0.911. Data processing using Structural Equation Modeling (SEM), LISREL 8.80 programme, the measurement model shows all items are valid and the structural model shows a fit and significant model. The results showed the similarity of husbands and wives handling pressure, using positive dyadic coping. The difference between husbands and wives on the perception of harmonious relationship satisfaction is the aspect of love and intimacy. With these findings, it is expected to be used by counsellors, family psychologists and others to guide couples to be harmonious